The effect of loading and velocity on muscle power output - Lee, C.-Y.; Chung, P.-H.; Shiang, T. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Muscular power is considered one of the main determinants of dynamic athletic performance. Two major methods for power training programs were low-resistance with fast speed and high-resistance with low speed. The purpose of this research was to investigating the influence of different intensities and velocity on muscle power output. The subjects were 10 males who had trained at least 3 month using bench press machine. All lifts were performed on a traditional ballistic bench press machine with a mass of 9.08-36.32 kg (increase in 9.08 kg steps). High-velocity lifting program (HI): The subjects performed 3 trials in each level load, as fast as possible from an elbow angle 90 degrees to full extension. Lower-velocity lifting program (LO): The metronome was used to keep movement speed at 20 rpm. The mean power and peak power were significantly different between HI and LO for all the loads, HI were significantly greater than LO. In addition, the mean power of 18.16 kg at high speed was significantly greater than mean power of 27.24 kg at low speed. Besides, the displacement decreased with the load increased in the different velocities. In conclusion, High velocity may be considered to be more important than heavy load to produce power output. The heavyresistance may reduce joint ROM in exercise.